Novel Method for Collecting Skin Microbiome Samples From Free‐Ranging Bottlenose Dolphin - Joseph J. Hansen; Jennifer C. G. Bloodgood; Brandi Kiel Reese; Thomas B. Waltzek; Kevin Barry; Thibaut Bouveroux; Carrie Sinclair; Kuttichantran Subramaniam; Keith D. Mullin; Ruth H. Carmichael (Marine Mammal Science, 2026)
Cetacean skin microbiome samples are traditionally collected by swabbing the skin of captured animals or using skin tissue from remote biopsies. The effects of different sampling methods are not well understood, and factors such as swab type and storage methods may affect the microbiome. The objective of this study was to determine if samples collected by swabbing biopsied skin from bottlenose dolphins yield sufficient microbial DNA for gene sequencing, while testing if commonly used sampling and storage methods affect the skin microbiome. Skin swab samples were collected during remote biopsy surveys with either a nylon flocked swab and flash frozen with liquid nitrogen or with a cotton swab and stored in RNAlater. Sequencing of the V3–V4 region of the 16S rRNA gene revealed swabs from dolphin skin biopsies yielded sufficient DNA to characterize the microbiome. We found no significant difference between the two sampling and storage methods tested, suggesting that studies using different techniques may be comparable. This work also demonstrates a novel technique to collect samples for interpretation of the skin microbiome of free‐ranging animals. Benefits of this method are that it can be done without capture and preserves valuable and typically scarce biopsy skin samples for other analyses.

Regional‐scale disturbances drive long‐term decline of inshore coral reef fish assemblages in the Great Barrier Reef Marine Park - Daniela M. Ceccarelli; Murray Logan; Richard D. Evans; Geoffrey P. Jones; Marji Puotinen; Caroline Petus; Garry R. Russ; Tane Sinclair‐Taylor; Maya Srinivasan; David H. Williamson (Global Change Biology, 2024)
Anthropogenic pressure is increasing the variety and frequency of environmental disturbance events, limiting recovery and leading to long‐term declines in wild plant and animal populations. Coral reefs and associated fish assemblages are inherently dynamic due to their susceptibility to a host of disturbances, but regional‐scale nuances in the drivers of long‐term change frequently remain poorly resolved. Here, we examine the effects of multiple potential drivers of change in coral reef fish assemblages across 4 inshore regions of the Great Barrier Reef Marine Park (GBRMP), Australia, over 12–14 years (2007–2021). Each region had a unique disturbance history, in conjunction with long‐term changes in physical and habitat variables. Phases of recovery were apparent in the years between disturbance events at all locations, but these were not long enough to prevent substantial declines in reef fish density (by 33%–72%) and species richness (by 41%–75%) throughout the study period. The main drivers of change in fish assemblages varied among regions; however, the most rapid changes followed cyclone and flood events. Limited recovery periods resulted in temporal shifts in fish species composition from typically coral‐associated to algae‐associated. Most trophic groups declined in density except farmers, grazers, omnivores and parrotfish. No‐take marine reserves (NTMRs) had small and inconsistent effects on total fish assemblages, but delivered benefits for fishery‐targeted piscivores. Our findings suggest that coral reef responses to local stressors and cumulative escalating climate change impacts are highly variable at regional scales, and that small NTMRs are unlikely to mitigate the impacts of increasingly frequent climatic disturbances. Nearshore coral reefs worldwide are high‐value habitats that are either already degraded or vulnerable to degradation and the loss of important fish groups. Global efforts to reduce greenhouse gas emissions must be coupled with effective local management that can support the functioning and adaptive capacity of coral reefs.

Saturn’s seasonal variability from four decades of ground-based mid-infrared observations - James S.D. Blake; L.N. Fletcher; G.S. Orton; A. Antuñano; M.T. Roman; Y. Kasaba; T. Fujiyoshi; H. Melin; D. Bardet; J.A. Sinclair; M. Es-Sayeh (Icarus, 2023)

Regional versus latitudinal variation in the life‐history traits and demographic rates of a reef fish, Centropyge bispinosa , in the Coral Sea and Great Barrier Reef Marine Parks, Australia - Jake R. Lowe; Samuel D. Payet; Hugo B. Harrison; Jean‐Paul A. Hobbs; Andrew S. Hoey; Brett M. Taylor; Tane H. Sinclair‐Taylor; Morgan S. Pratchett (Journal of Fish Biology, 2021)
Environmental temperature is an important determinant of physiological processes and life histories in ectotherms. Over latitudinal scales, variation in temperature has been linked to changes in life‐history traits and demographic rates, with growth and mortality rates generally being greatest at low latitudes, and longevity and maximum length being greater at higher latitudes. Using the two‐spined angelfish, Centropyge bispinosa , as our focal species, we compared growth patterns, growth rates, longevity, mortality, asymptotic length and maximum length across 22 reefs that span 13° of latitude within the Great Barrier Reef Marine Park (GBRMP) and the Coral Sea Marine Park (CSMP), Australia. We found no predictable latitudinal variation in mortality rates, growth patterns, growth rates, asymptotic or maximum length of C. bispinosa at regional to biogeographic scales. However, C. bispinosa consistently exhibited reduced longevity at lower, warmer latitudes within the CSMP. The greatest differences in mean maximum length of C. bispinosa were between continental (GBRMP) and oceanic (central CSMP) reefs of similar latitude, with individuals being larger on average on continental versus oceanic reefs. The lack of predictable life‐history and demographic variation in C. bispinosa across a 13° latitudinal gradient within the CSMP, coupled with differences in mean maximum length between continental and oceanic reefs at similar latitudes, suggest that local environmental conditions have a greater influence than environmental temperature on the demographic rates and life‐history traits of C. bispinosa .

Growth patterns of specialized reef fishes distributed across the Red Sea to Gulf of Aden - Joseph D. DiBattista; Brett M. Taylor; Jean-Paul A. Hobbs; Tane H. Sinclair-Taylor; Darren J. Coker; Elizabeth D. L. Trip; J. Howard Choat; Diego Lozano-Cortés; Nora M. Kandler; Michael L. Berumen (Environmental Biology of Fishes, 2021)

Comparative demography of commercially important species of coral grouper, Plectropomus leopardus and P. laevis , from Australia's great barrier reef and Coral Sea marine parks - Samuel D. Payet; Jake R. Lowe; Bruce D. Mapstone; Morgan S. Pratchett; Tane H. Sinclair‐Taylor; Brett M. Taylor; Peter A. Waldie; Hugo B. Harrison (Journal of Fish Biology, 2020)
Understanding the spatial and environmental variation in demographic processes of fisheries target species, such as coral grouper (Genus: Plectropomus ), is important for establishing effective management and conservation strategies. Herein we compare the demography of Plectropomus leopardus and P. laevis between Australia's Great Barrier Reef Marine Park (GBRMP), which has been subject to sustained and extensive fishing pressure, and the oceanic atolls of Australia's Coral Sea Marine Park (CSMP), where there is very limited fishing for reef fishes. Coral grouper length‐at‐age data from contemporary and historical otolith collections across 9.4 degrees of latitude showed little difference in lifetime growth between GBRMP and CSMP regions. Plectropomus laevis populations in GBRMP reefs had significantly higher rates of total mortality than populations in the CSMP. Mean maximum lengths and mean maximum ages of P. laevis were also smaller in the GBRMP than in the CSMP, even when considering populations sampled within GBRMP no‐take marine reserves (NTMRs). Plectropomus leopardus , individuals were on average smaller on fished reefs than NTMRs in the GBRMP, but all other aspects of demography were broadly similar between regions despite the negligible levels of fishing pressure in the CSMP. Similarities between regions in growth profiles and length‐at‐age comparisons of P. laevis and P. leopardus suggest that the environmental differences between the CSMP and the GBRMP may not have significant impacts on lifetime growth. Our results show that fishing may have influenced the demography of coral grouper on the GBR, particularly for the slower growing and longer lived species, P. laevis .

Seagrass Restoration Is Possible: Insights and Lessons From Australia and New Zealand - Yi Mei Tan; Oliver Dalby; Gary A. Kendrick; John Statton; Elizabeth A. Sinclair; Matthew W. Fraser; Peter I. Macreadie; Chris L. Gillies; Rhys A. Coleman; Michelle Waycott; Kor-jent van Dijk; Adriana Vergés; et al. (Frontiers in Marine Science, 2020)

The limitations of some European healthcare databases for monitoring the effectiveness of pregnancy prevention programmes as risk minimisation measures - R. A. Charlton; V. Bettoli; H. J. Bos; A. Engeland; E. Garne; R. Gini; A. V. Hansen; L. T. W. de Jong-van den berg; S. Jordan; K. Klungsøyr; A. J. Neville; A. Pierini; et al. (European Journal of Clinical Pharmacology, 2018)

Breakdown in assortative mating leads to hybrid swarm in pygmy angelfishes - J. P. A. Hobbs; J. D. DiBattista; T. H. Sinclair-Taylor (Coral Reefs, 2018)

Spatial patterns of cryptobenthic coral-reef fishes in the Red Sea - Darren J. Coker; Joseph D. DiBattista; Tane H. Sinclair-Taylor; Michael L. Berumen (Coral Reefs, 2018)

Assessing the utility of eDNA as a tool to survey reef-fish communities in the Red Sea - Joseph D. DiBattista; Darren J. Coker; Tane H. Sinclair-Taylor; Michael Stat; Michael L. Berumen; Michael Bunce (Coral Reefs, 2017)

Comparative phylogeography of reef fishes from the Gulf of Aden to the Arabian Sea reveals two cryptic lineages - Joseph D. DiBattista; Michelle R. Gaither; Jean-Paul A. Hobbs; Pablo Saenz-Agudelo; Marek J. Piatek; Brian W. Bowen; Luiz A. Rocha; J. Howard Choat; Jennifer H. McIlwain; Mark A. Priest; Tane H. Sinclair-Taylor; Michael L. Berumen (Coral Reefs, 2017)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

A review of contemporary patterns of endemism for shallow water reef fauna in the Red Sea - Joseph D. DiBattista; May B. Roberts; Jessica Bouwmeester; Brian W. Bowen; Darren J. Coker; Diego F. Lozano‐Cortés; J. Howard Choat; Michelle R. Gaither; Jean‐Paul A. Hobbs; Maha T. Khalil; Marc Kochzius; Robert F. Myers; et al. (Journal of Biogeography, 2016)
Aim The Red Sea is characterised by a unique fauna and historical periods of desiccation, hypersalinity and intermittent isolation. The origin and contemporary composition of reef‐associated taxa in this region can illuminate biogeographical principles about vicariance and the establishment (or local extirpation) of existing species. Here we aim to: (1) outline the distribution of shallow water fauna between the Red Sea and adjacent regions, (2) explore mechanisms for maintaining these distributions and (3) propose hypotheses to test these mechanisms. Location Red Sea, Gulf of Aden, Arabian Sea, Arabian Gulf and Indian Ocean. Methods Updated checklists for scleractinian corals, fishes and non‐coral invertebrates were used to determine species richness in the Red Sea and the rest of the Arabian Peninsula and assess levels of endemism. Fine‐scale diversity and abundance of reef fishes within the Red Sea were explored using ecological survey data. Results Within the Red Sea, we recorded 346 zooxanthellate and azooxanthellate scleractinian coral species of which 19 are endemic (5.5%). Currently 635 species of polychaetes, 211 echinoderms and 79 ascidians have been documented, with endemism rates of 12.6%, 8.1% and 16.5% respectively. A preliminary compilation of 231 species of crustaceans and 137 species of molluscs include 10.0% and 6.6% endemism respectively. We documented 1071 shallow fish species, with 12.9% endemic in the entire Red Sea and 14.1% endemic in the Red Sea and Gulf of Aden. Based on ecological survey data of endemic fishes, there were no major changes in species richness or abundance across 1100 km of Saudi Arabian coastline. Main conclusions The Red Sea biota appears resilient to major environmental fluctuations and is characterized by high rates of endemism with variable degrees of incursion into the Gulf of Aden. The nearby Omani and Arabian Gulfs also have variable environments and high levels of endemism, but these are not consistently distinct across taxa. The presence of physical barriers does not appear to explain species distributions, which are more likely determined by ecological plasticity and genetic diversity.

Diversity enhances carbon storage in tropical forests - L. Poorter; M. T. van der Sande; J. Thompson; E. J. M. M. Arets; A. Alarcón; J. Álvarez‐Sánchez; N. Ascarrunz; P. Balvanera; G. Barajas‐Guzmán; A. Boit; F. Bongers; F. A. Carvalho; et al. (Global Ecology and Biogeography, 2015)
Aim Tropical forests store 25% of global carbon and harbour 96% of the world's tree species, but it is not clear whether this high biodiversity matters for carbon storage. Few studies have teased apart the relative importance of forest attributes and environmental drivers for ecosystem functioning, and no such study exists for the tropics. Location Neotropics. Methods We relate aboveground biomass ( AGB ) to forest attributes (diversity and structure) and environmental drivers (annual rainfall and soil fertility) using data from 144,000 trees, 2050 forest plots and 59 forest sites. The sites span the complete latitudinal and climatic gradients in the lowland Neotropics, with rainfall ranging from 750 to 4350 mm year −1 . Relationships were analysed within forest sites at scales of 0.1 and 1 ha and across forest sites along large‐scale environmental gradients. We used a structural equation model to test the hypothesis that species richness, forest structural attributes and environmental drivers have independent, positive effects on AGB . Results Across sites, AGB was most strongly driven by rainfall, followed by average tree stem diameter and rarefied species richness, which all had positive effects on AGB . Our indicator of soil fertility (cation exchange capacity) had a negligible effect on AGB , perhaps because we used a global soil database. Taxonomic forest attributes (i.e. species richness, rarefied richness and Shannon diversity) had the strongest relationships with AGB at small spatial scales, where an additional species can still make a difference in terms of niche complementarity, while structural forest attributes (i.e. tree density and tree size) had strong relationships with AGB at all spatial scales. Main conclusions Biodiversity has an independent, positive effect on AGB and ecosystem functioning, not only in relatively simple temperate systems but also in structurally complex hyperdiverse tropical forests. Biodiversity conservation should therefore be a key component of the UN Reducing Emissions from Deforestation and Degradation strateg y.

When biogeographical provinces collide: hybridization of reef fishes at the crossroads of marine biogeographical provinces in the Arabian Sea - Joseph D. DiBattista; Luiz A. Rocha; Jean‐Paul A. Hobbs; Song He; Mark A. Priest; Tane H. Sinclair‐Taylor; Brian W. Bowen; Michael L. Berumen (Journal of Biogeography, 2015)
Aim Suture zones are areas where closely related species from different biogeographical regions come into contact and interbreed. This concept originated from the study of terrestrial ecosystems but it remains unclear whether a similar phenomenon occurs in the marine environment. Here we investigate a potential suture zone from a previously unknown hybrid hotspot at the Socotra Archipelago (Yemen), located in the Arabian Sea, where fauna from the Red Sea, Gulf of Aden, Arabian Sea, western Indian Ocean and greater Indo‐Polynesian Province intersect. Location Red Sea, Gulf of Aden, Arabian Sea and Indian Ocean. Methods Putative hybrid reef fish were identified based on intermediate coloration and morphology. Underwater observations and collections were conducted to determine: (1) whether parent species form heterospecific social groups or breeding pairs; (2) the sex and reproductive status of morphologically intermediate individuals; and (3) whether parent species were forming mixed species associations owing to a dearth of conspecific partners. To support hybrid status, morphologically intermediate and parental individuals were genotyped using mitochondrial DNA cytochrome c oxidase subunit I ( COI ), nuclear recombination‐activating gene 2 ( RAG 2 ) and the nuclear TMO ‐4C4 (TMO) gene. Results We observed putative hybrids involving 14 species from four reef fish families at Socotra. Most cases involved a parental species with a restricted distribution (e.g. Red Sea or Arabian Sea) and a broadly distributed Indo‐Pacific species. In most cases, at least one of the parent species was rare at Socotra. Hybrid gene flow was largely unidirectional, and although introgression was rare, we found evidence that some butterflyfish and surgeonfish hybrids were fertile and formed breeding groups with parental species. Main conclusions The rate of hybrid discovery at Socotra is much greater than that recorded elsewhere in the marine environment and involved both allopatric and sympatric species. This study highlights the importance of biogeographical location, reef habitat, environmental conditions and abundance disparities at Socotra in potentially facilitating hybridization among reef fishes at the edge of their distribution.

The potential role of microRNAs in regulating gonadal sex differentiation in the chicken embryo - Andrew D. Cutting; Stephanie C. Bannister; Tim J. Doran; Andrew H. Sinclair; Mark V. L. Tizard; Craig A. Smith (Chromosome Research, 2012)

Incorporation of indigenous knowledge and perspectives in agroforestry development - D. H. Walker; F. L. Sinclair; B. Thapa (Agroforestry Systems, 1995)

Incorporation of indigenous knowledge and perspectives in agroforestry development - B. Thapa; F. L. Sinclair; D. H. Walker (Agroforestry Systems, 1995)